3(х²+1/х²)+5(х+1/х)=2

3(х²+1/х²)+5(х+1/х)=2
Гость
Ответ(ы) на вопрос:
Гость
3*(x^2+1/x^2)+5*(x+1/x) = 2 3х²+5х+[latex] \frac{5}{x} [/latex] +[latex] \frac{3}{x^2} [/latex] =2 3x²+5x+[latex] \frac{5}{x} [/latex] +[latex] \frac{3}{x^2} [/latex]-2=0 [latex] \frac{3x^4+5x^3-2x^2+5x+3}{x^2} =0[/latex] [latex] \frac{1}{x^2} =0[/latex] [latex]3x^4+5x^3-2x^2+5x+3=0[/latex] x²-x+1=0 3x²+8x+3=0 Возможные решения: -[latex]- \frac{ \sqrt{7}+4 }{3} ; \frac{ \sqrt{7} -4}{3} [/latex] Ответ: x=-√(7)/3-4/3, x=√(7)/3-4/3;
Не нашли ответ?
Ответить на вопрос
Похожие вопросы